How individual social capital affects residents’ satisfaction with medical services: Based on the evidence from urban residents in China - Wang, Wenbin; Cao, Yang (Frontiers in Psychology, 2022)
Residents’ satisfaction with medical services has commonly been treated as both a medical and psychosocial process. The influence of psychosocial factors on residents’ satisfaction with medical treatment is generally considered as important as that of medical factors. However, the effect of individual social capital on residents’ satisfaction after medical treatment—an important psychosocial variable that may influence health status and access to medical services—has not received sufficient attention. This study used the questionnaire survey data of urban residents in eight Chinese cities in 2014 to investigate how individual social capital affects residents’ satisfaction with medical services over the past year. The results revealed a negative impact of individual social capital on residents’ overall satisfaction with medical services. In addition, the use of individual social capital significantly improved residents’ satisfaction with medical resources and significantly reduced residents’ satisfaction with the medical system. Moreover, the negative impact of individual social capital on residents’ overall satisfaction with medical services was greater for individuals with a lower likelihood of using this capital, which may lead to unequal allocation of medical resources and long-term life satisfaction. The heterogeneous impact and mechanism of individual social capital on residents’ satisfaction with medical services was confirmed under the premise of self-selection bias.